Using Convergent Parallel Mixed Methods and Datasets for Science, Technology, and Innovation Policy Dynamics Research in Indonesia - Prakoso Bhairawa Putera; Suryanto Suryanto; Sinta Ningrum; Ida Widianingsih; Yan Rianto (Universitas Gadjah Mada, 2022)
The application of mixed methods has been widely implemented in several studies, particularly in the field of public policy; however, the implementation of convergent parallel mixed methods has been limited. Thus, such methods are appropriate to reveal the science, technology, and innovation (STI) policy dynamics in Indonesia during the 1945–2020 period, as policy dynamics research attempts to reveal the evolution of the changes regarding the policy itself. The following five concepts are analyzed through convergent parallel mixed methods: 1) regime/government change, 2) institutional change/transformation, 3) change in policy issuance, direction, and content, 4) actor role and existence, and 5) policy object input and output. This article discusses the method details, from the paradigm, research dataset, and technique selection for collecting and analyzing research data to the research implementation.